STRATEGIC TALENT MANAGEMENT AS A FACTOR FOR ENHANCING ENTERPRISE COMPETITIVENESS (Development Service Industry Management, 2025)
The article investigates strategic talent management as a critical factor in enhancing the competitiveness of enterprises under contemporary socio-economic challenges. The study provides a comprehensive analysis of the theoretical foundations of talent management, tracing the historical development of the concept and examining key approaches and models applied in both international and domestic practices. The core functions of talent management are explored, including recruitment, onboarding, professional development, motivation, and employee retention, alongside the integration of these processes into corporate strategy, taking into account the specific characteristics of the Ukrainian labor market. Special attention is paid to modern management tools, such as HR analytics, digital competency assessment systems, learning management systems (LMS), artificial intelligence, and Agile Talent Management models, which contribute to the effective attraction, development, and retention of personnel. Empirical data are presented on the impact of talent management strategies on employee engagement, productivity, turnover rates, corporate culture, and the long-term competitive advantages of enterprises. The study also discusses practical aspects of strategy implementation, including flexible working arrangements, well-being and social support programs, coaching, and mentoring. Furthermore, it emphasizes the importance of integrating quantitative and qualitative metrics, such as Talent KPIs, to monitor and evaluate the effectiveness of talent management initiatives. Key directions for future research are identified, including the development of integrated talent management systems leveraging analytical and digital tools, the adaptation of models to the specific context of Ukrainian organizations, and the assessment of strategic talent management’s influence on sustainable enterprise development. The findings underscore that strategic talent management is not only a tool for optimizing human resource processes but also a fundamental element in achieving organizational resilience, innovation, and long-term value creation in a rapidly changing socio-economic environment.
Keywords: strategic talent management; competitiveness; human resource development; employee retention; digital technologies; sustainable development